Biodegradable, solvent-free photocrosslinkable PLLA resin formulations for additive manufacturing - Pal, Shibam; Asha, S. K. (Macromolecular Chemistry and Physics, 2022)
Acrylate end-functionalized linear and star poly l-lactide (PLLA) based aliphatic, photocurable oligomeric crosslinkers are developed, which are formulated with hydroxyl (ethyl)methacrylate (HEMA) as a biodegradable reactive diluent to demonstrate successful application for solvent-less 3D printing using digital light processing (DLP) technique as well as a custom-designed direct ink writing 3D printer. The resin formulation for 3D printing is optimized using spot curing, photodifferential scanning calorimetry and cure depth analysis. The 3D printed parts exhibit promising mechanical property along with improved hydrophilicity and biodegradability. The development of new photocurable resin formulations are expected to meet the growing demand for raw materials that can be applied for developing custom designed bio implantable objects.
Keywords: 3D printing; biodegradable materials; digital light processing; L-Lactide; photocurable materials